The Measure of Madness : Philosophy of Mind, Cognitive Neuroscience, and Delusional Thought - Gerrans, Philip, 1959- (Book collections on Project MUSE., 2014)
This title offers a novel explanation of delusion. Over the last two decades, philosophers and cognitive scientists have investigated explanations of delusion that interweave philosophical questions about the nature of belief and rationality with findings from cognitive science and neurobiology. The book argues that once we fully describe the computational and neural mechanisms that produce delusion and the way in which conscious experience and thought depend on them, the concept of delusional belief retains only a heuristic role in the explanation of delusion.